AutoCAD 2016 3D Modeling - Hamad, Munir M. (Mercury Learning and Information, 2016)
Using both metric and imperial units to illustrate the myriad tools for this popular application, this reference provides new and seasoned users with step-by-step procedures on creating and modifying 3D models, working with cameras and lights, assigning materials to objects, rendering, and printing. --